Language Style Used by Characters in Moxie Movie - Waisnawati, Luh Komang Anggi; Indrawati, Luh Ketut Mas; Artawa, Ketut (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2023)
This research discusses the types of language style that are used by the characters in the movie as well as their functions. By knowing the style of language as well as the function of the language, then there will be no misinterpretation between the speaker and listener. The data were collected by using documentation methods and note-taking techniques. In analyzing the data, this study used a descriptive qualitative method. The data were analyzed by using a table. Informal technique was applied in presenting the analysis. This study used the theory from Joos (1967) in analyzing the language style which consisted of frozen style, formal style, consultative style, casual style, and intimate style. Meanwhile the theory from Holmes (2013) was used to analyze the language functions which included expressive, directive, referential, metalinguistic, poetic, and phatic. The result of this study showed there were four types of language style used by the characters in the Moxie movie. There were 4 data for formal style, 6 data for consultative style, 15 data for casual style, and 12 data for intimate style. Furthermore, there were three functions of language found in the movie, they were expressive, referential, and phatic functions. Meanwhile, directive, metalinguistic, and poetic functions were not found from the characters utterances.   Keywords : Sociolinguistics, Language Style, Speech Function, Moxie Movie